Methodology For Developing The Physical Education Of Primary School Children (Eurasian Research Bulletin, 2024)
This article examines the methodology for developing the physical activity of primary school children by analyzing existing scientific literature, creating a new methodology, and successfully enhancing the physical movement capabilities of primary school-aged children.